The evaluation of postoperative objective and subjective refraction for premium intraocular lenses - Fikret Ucar; Servet Cetinkaya (Revista Brasileira de Oftalmologia, 2021)
Abstract Purpose: To evaluate six different premium IOLs retrospectively in respect to both subjective and objective refraction after cataract operation. Methods: Five hundreds and seventy eyes of 285 patients with bilateral cataract who had undergone phacoemulsification and IOL implantation operation between February 2017 and September 2018 were enrolled in this study. The mean age of the patients was 57.78 ± 7.49 (41-71) years. Out of 285 patients 137 were male (48.07%) and 148 were female (51.93%). TheIOLsusedare: RayOne Trifocal (Rayner, Worthing, UK), Lucidis (Swiss Advanced Vision, Neuchâtel, Switzerland), PanOptix (Alcon, Fort Worth, USA), LentisMplus (Oculentis, Berlin, Germany), TecnisSymfony (Abbott, Illinois, USA) and Acriva Trinova (VSY Biotechnology, Istanbul, Turkey). Results: There were no significant differences among the groups regarding age, sex, axial length, the mean preoperative and postoperative uncorrected visual acuity (UCVA), best-corrected visual acuity (BCVA), the mean preoperative spherical equivalent (SE) and the mean postoperative SE (subjective measurement) (P> .05). The postoperative refractions measured with autorefractometer were more myopic than subjective refractions in all patients except the patients who had PanOptix IOL. In postoperative twelfth month, the mean UCVA arrived 0.00 logMAR in 405 eyes (78.48%) , however, the mean autorefractometric measurement was -1.28 ± 1.02 (0.00_-2.75) D. Conclusion: The autorefractometer measurements of all patients who had premium IOLs except PanOptix IOL were not coherent with their visual acuities postoperatively. The ophthalmologists and/or optometrists should be careful while examining these types of patients.